Distribution, sources and health risk assessment of polycyclic aromatic hydrocarbons in urban soils under different landform conditions of Taiyuan, China - Liu, Liwen; Chen, Xiangling; Duan, Yonghong; Wu, Zhangwei; Xu, Lishuai (Frontiers in Environmental Science, 2024)
Public concern about polycyclic aromatic hydrocarbons (PAHs) is rising due to their potential carcinogenic, teratogenic, and mutagenic effects. This study assessed PAHs in Taiyuan City's plain and mountain soil, investigating concentrations, distribution, sources, and carcinogenic risk.Σ21PAHs concentrations in plain topsoil ranged from 133.2 to 6410.6 ng/g (mean 1444.7 ng/g), and in mountain soil from 66.5 to 2250.2 ng/g (mean 585.5 ng/g). Approximately 55.1% of plain and 19.0% of mountain soil samples had contamination levels exceeding 600 ng/g. In plain soil, 4-ring and 5-ring PAHs dominated, while 2-ring and 3-ring PAHs were prevalent in mountain soil. Polluted areas in Taiyuan were primarily centered in the central-north, with higher content closer to industrial or business districts. PAH isomer ratios and principal component analysis/multiple linear regression (PCA/MLR) indicated coal combustion as the main PAH source, followed by coke production, vehicle emissions, and biomass combustion. Incremental lifetime cancer risks (ILCRs) showed Taiyuan's PAH-related cancer risks were generally low, though heavily contaminated areas exhibited moderate risks. Plain regions had three times higher cancer risk than mountains, with children facing higher risk than adults. These findings highlight the need to consider PAH pollution while enhancing urban environmental quality.